Enhancing Cr(VI) bioreduction via Na+-stimulated intracellular energy metabolism and electron transfer using methane as electron donor - Lianfu Liang; Xiaofeng Fu; Yuqing Ding; Keying Liu; Rui Lin; Zhaojin Chen (Bioresource Technology, 2027)

Biochar enhances anaerobic oxidation of methane coupled with Cr(VI) reduction: Pyrolysis temperature-dependent electron transfer pathways and regulatory mechanisms - Lianfu Liang; Yepu Li; Xiaofeng Fu; Rui Lin; Keying Liu; Zhiqiang Zhao (Bioresource Technology, 2026)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Infectious spleen and kidney necrosis virus promotes replication organelle formation and sphingolipid biosynthesis to facilitate viral replication - Wenwen Xiao; Xiaozhe Fu; Yilin Zhu; Qiquan Liu; Qiang Lin; Hongru Liang; Xia Luo; Yinjie Niu; Baofu Ma; Ningqiu Li (Fish & Shellfish Immunology, 2026)

Aromatic protein-like recognition enables rapid prediction of sludge deep dewaterability - Jianting Liu; Zhihua Mo; Qingyi Lei; Haowen Guo; Shengye Lin; Zhijian Fu; Jialin Liang; Shuiyu Sun (Bioresource Technology, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Microbial insights into a high water-quality dependent freshwater snail: Geographical origin and rearing mode shape the gut antibiotic resistance gene profile of Sulcospira hainanensis - Lingtong Ye; Chen Chen; Shengli Fu; Jie Lu; Tuo Yao; Huajian Lin; Zhifu Liang; Huan Li; Jinxia Peng; Zhenhua Ma (Environmental Pollution, 2026)

Developing a fusion algorithm based on UAV and mobile monitoring to quantify black carbon emissions from various types of planned straw residue burning - Jing Fu; Weiwei Chen; Chong Hui; Xue Yang; Lin Liang; Bowen Shi (Atmospheric Environment, 2026)

Absolute configurations and anti-bacterial activity of two century-old maleidrides - Rongfang Qu; Chenyu Wu; Wenhao Mu; Yuxia Lou; Weibing Jiang; Minfeng Jin; Lin-Fu Liang; Fan Yang (Natural Product Research, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Global lactylation is downregulated despite lactate accumulation: lactylome data and functional insights during ISKNV infection - Zhourui Sun; Yinjie Niu; Xiaozhe Fu; Qiang Lin; Xianglin Cao; Hongru Liang; Xia Luo; Baofu Ma; Wenwen Xiao; Ningqiu Li; Jianjun Chen (Fish & Shellfish Immunology, 2026)

Tectonostratigraphic evolution of the Northeast South China Sea Rifted Margin: From Mesozoic orogeny to Present - Mateus Rodrigues de Vargas; Geoffroy Mohn; Julie Tugend; Nick Kusznir; Andrew Lin; Liang-Fu Lin (Earth-Science Reviews, 2026)

Biomimetic pangolin-scale sustainable cellulose-based composite paper serves as a multifunctional platform for portable radiative cooling - Fengqiong Jiang; Yuancheng Zhang; Zhen Wang; Tao Zheng; Yuntong Liang; Chuanhui Xu; Bai Huang; Lihua Fu; Baofeng Lin (Carbohydrate Polymers, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Integrated analysis of dynamic changes in volatile and non-volatile compounds in Chuan Chenpi (Citrus reticulata ‘Dahongpao’) during aging by GC-IMS and UPLC-MS/MS - Jialiang Zou; Huangsheng Zhang; Liang Zhao; Huanhuan Xu; Lin Chen; Hongping Chen; Fu Wang; Yuan Hu; Youping Liu (Food Chemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Ejecta from Chaffee S Crater in Chang’E-6 Landing Site Constrained by Seifertite-Bearing Norite - Zhan Zhou; Sen Hu; Yubing Gao; Linxi Li; Huicun He; Liang Gao; Mengfan Qiu; Lixin Gu; Xu Tang; Xiaoguang Li; Wei Yang; Yangting Lin; et al. (Journal of Earth Science, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Iron and calcium interaction for soil As remediation in As waste mine site: Risk assessment and In-situ stabilization - Yuliang Zhang; Sheng Li; Pingfeng Fu; Fangxiang Tu; Tao Zhang; Huiqun Yu; Huifen Yang; Tianli Xue; Xi Qin; Chonggao Wei; Lin Liang (Environmental Pollution, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Structural vibration analysis and safety assessment of centrifuges under hypergravity environments - Chengpeng Hong; Guanwen Liang; Li Bi; Haoran Fu; Zizhuang Yan; Kuigen Lin; Yunmin Chen (Engineering Structures, 2026)

Correction: Metagenomics reveals diverse community of putative mercury methylators across different biogeochemical niches in Sansha Yongle blue hole - Heyu Lin; Xiao-Yu Zhu; Chun-Xu Xue; Peng Yao; Liang Fu; Zuosheng Yang; Xiao-Hua Zhang; John W. Moreau (Marine Life Science & Technology, 2026)

Stable network complexity between bacterial community and dissolved organic matter remains under three-year consecutive nitrogen addition - Xiaochun Yuan; Quanxin Zeng; Qiufang Zhang; Cheng-Chung Liu; Junjian Wang; Liang Zeng; Kaimiao Lin; Chaoliang Chen; Weifeng Guo; Jiacong Zhou; Juyan Cui; Xiaoli Gao; et al. (Applied Soil Ecology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Finite-volume converged ENO scheme with adaptive mesh resolution for steady-state compressible flow simulation - Tian Liang; Lin Fu (Computer Physics Communications, 2026)

Phytochemicals and health-promoting evaluations of Ophiorrhiza puffii , a chinese endemic plant - Qing Bu; Qi-Bin Yang; Zeng-Yue Ge; Ze-Xiong Shi; Lin-Fu Liang (Natural Product Research, 2026)

FGF2 Enhances MSCs Secretome Therapy for Skin Photoaging by Delaying Senescence via iNAMPT/AMPK Signaling and Facilitating eNAMPT-Mediated Regenerative Crosstalk - Yixin Zhang; Manping Lu; Jieqing Ouyang; Lin Liang; Fan Li; Zhihan Pei; Lihao Chen; Miaoman Ye; Jiajie Tan; Liwei Xiang; Lijing Kong; Long Huang; et al. (Stem Cell Reviews and Reports, 2026)

Effects of inflammatory markers and sleep quality in stroke patients by reducing residential PM2.5 levels: A case-crossover intervention study - Wen-Hua Lee; Chen-Ta Lin; Pei-Chih Wu; Sheng-Fu Liang; Cheng-Yu Lin; Yu-Chun Wang; Shih-Chun Candice Lung; Tain-Junn Cheng (Science of The Total Environment, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

Highly stable, temperature- and humidity-responsive eutectogels for long-term sustained release of ClO₂ - Qiao yuan Luo; Tianrui Zhou; Zhen Wang; Yuntong Liang; Lihua Fu; Chuanhui Xu; Bai Huang; Baofeng Lin (Chemical Engineering Journal, 2026)

Effect of CPAP treatment on subjective cognitive decline in patients with mild obstructive sleep apnea syndrome - Liang Tan; Xin Zhang; Zhijian Fu; Chunyao Dong; Chang Zhou; Caiyun Hou; Yuanyuan Lin; Xiaolei Wang; Li Li; Jin Zhou (Sleep and Biological Rhythms, 2026)
There is no consensus on whether to use continuous positive airway pressure (CPAP) treatment for mild obstructive sleep apnea syndrome (OSAS). Our study aims to observe the efficacy and necessity of using CPAP treatment in mild OSAS patients complicated with subjective cognitive decline (SCD). From August 2021 to July 2022, patients with mild OSAS and SCD were randomized to the control group or the CPAP group, and followed up for 3 months. The primary results were evaluated using subjective cognitive decline questionnaire (SCD-Q), the Huashan version of the Auditory Verbal Learning Test (AVLT-H), and animal fluency test (AFT), which were tested at admission and three months after treatment, respectively. And plasma Aβ1–40 and Aβ1–42 levels were also measured at admission and 3 months after treatment. A total of 110 patients completed the final study, with 55 in the control group and 55 in the CPAP group. No significant differences in demographic data, Laboratory tests, AHI index, SCD-Q, AVLT-H, and AFT scores between the two groups before treatment. The SCD-Q score of patients in CPAP group significantly decreased after 3 months of treatment and was significantly lower than that of control group ( P <0.05). And the immediate memory score of AVLT-H in the treatment group was significantly increased after 3 months of treatment ( P < 0.05). The Aβ1–42/Aβ1–40 ratio in the treatment group significantly decreased after 3 months of treatment, and was significantly lower than that of control group ( P <0.05). Furthermore, there was linear correlation between SCD-Q score and Aβ1–42/Aβ1–40 ratio in all patients after 3 months of treatment ( P <0.001, r =0.584). Our findings suggested that CPAP treatment can significantly decrease the Aβ1–42/Aβ1–40 ratio, and improve SCD, which may play an important role in the prevention of dementia, but further research are warranted.

Metagenomics reveals diverse community of putative mercury methylators across different biogeochemical niches in Sansha Yongle blue hole - Heyu Lin; Xiao-Yu Zhu; Chun-Xu Xue; Peng Yao; Liang Fu; Zuosheng Yang; Xiao-Hua Zhang; John W. Moreau (Marine Life Science & Technology, 2025)
Methylmercury (MeHg) is a potent neurotoxin and bioaccumulates in food webs. Microbial transformation of inorganic mercury (Hg) produces most of the MeHg in the marine environment. The gene pair hgcAB encodes for Hg methylation, a process predominantly attributed to anaerobic bacteria. However, recent studies indicate the formation of methylmercury in low-oxygen zones within marine water columns, although the mechanisms remain poorly understood. “Blue holes” are marine sinkholes containing redox gradients stratified with depth and high microbial diversity across a range of biogeochemical cycles. Here, we present the first metagenomic analysis focused on the potential for Hg methylation in a blue hole ecosystem. Yongle Blue Hole (YBH), currently the world’s deepest known blue hole, was selected as a representative site to investigate the genetic potential for Hg methylation and to explore the functional capabilities of putative Hg-methylators within this unique environment. Metagenomic analysis showed that the anoxic sulfidic deep water was likely to be a hotspot for Hg methylation, driven by abundant and diverse Deltaproteobacteria. In the suboxic intermediate layer, Nitrospina and Myxococcota dominated the Hg-methylating community. Furthermore, Hg methylators were found to have different lifestyles (free-living or particle-associated) and to occupy distinct ecological niches within the YBH. In addition, the contribution of sinking particles to Hg methylation, especially in the deep anoxic water column, was highlighted. Our study unveils the biodiversity and survival strategies of Hg methylators across distinct environments. The findings suggest that blue holes could serve as model stratified ecosystems for studying Hg methylation processes across different habitats.

Network pharmacology, molecular docking and experimental validation to elucidate the anti-ulcerative colitis mechanism of Rosa roxburghii Tratt. leaves - Ming-Liang Luo; Shuang Zhang; Qing-Yong Wang; Ling-Wei Fu; Li-Juan Xiang; Chang Lin; Xin Yin (Natural Product Research, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Dose effects of polyethylene microplastics on the degradation of phenanthrene in agricultural soils and its underlying mechanisms - Chengyue Liang; Weilian Fu; Lin Tian; Wumei Xu; Yong Zhang; Tai Xiang; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

Active cellulose-based film with synergistic enhanced photothermal antibacterial effects by Fe-doped ZIF-8 and EGCG for efficient litchi preservation - Wenxin Zhao; Yuntong Liang; Yuancheng Zhang; Yongfu Deng; Hao Fu; Xu Yuan; Zhen Wang; Xiaohe Lu; Baofeng Lin (Chemical Engineering Journal, 2025)

Impact of SNP Variants in PON-1 or UGT1A1 on Iron Chelation Therapy Outcomes and Zinc Status in Thalassemia Major Patients - Meng-Yao Lu; Wan-Fu Tsai; Chang-Shiann Wu; Chien-Sheng Wang; Nailis Syifa; Mong-Liang Lu; Jiahn-Haur Liao; Wei J. Chen; Kai-Hsin Lin; Tzu-Hua Wu (Biological Trace Element Research, 2025)

Chemotaxonomically significant phytochemicals with α-glucosidase and tyrosinase inhibitory activities from Chinese endemic plant Ophiorrhiza hunanica - Qing Bu; Qi-Bin Yang; Can-Qi Liu; Zeng-Yue Ge; Xiao-Wen Liao; Lei Wu; Lin-Fu Liang (Natural Product Research, 2025)

Comprehensive analysis of volatile flavor components in pear fruit spanning the entire development stages - Lu Shi; Wanlin He; Menghua Lin; Xiaohui Fu; Yahui Li; Ying Liang; Zhiyong Zhang (Food Chemistry, 2025)

Mechanisms of endothelial senescence and vascular aging - Qiao Li; Zonghao Qian; Yuzhen Huang; Xiao Yang; Jiankun Yang; Nanyin Xiao; Guangyu Liang; Heng Zhang; Yanguang Fu; Yan Lin; Cuntai Zhang; Anding Liu (Biogerontology, 2025)

Role of Dorsolateral Prefrontal Cortex During Motor Preparation on Anticipatory Postural Adjustments - Jiajia Yang; Guifang Zhang; Xiaoyu Gao; Xue Cheng; Zengming Hao; Jinjin Ma; Nanhe Lin; Ruochen Fu; Wai Leung; Ambrose Lo; Yan Li; Hao Xie; et al. (Brain Topography, 2025)

Assembly processes of rare and abundant microbial taxa are closely related to bacterial and fungal functionality during desert vegetation reestablishment - Zhouchang YU; Wei ZHANG; Pian DUO; Ying ZHANG; Xingfang TIAN; Lin SUN; Yuzheng GU; Junhong ZHANG; Jiaxing SONG; Ahejiang SAILIKE; Yujie LIANG; Rong FU; et al. (Pedosphere, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

A fully Coupled thermal-hydrodynamic–chemical numerical model for simulating gas hydrate-bearing sediments dissociation based on peridynamic differential operator method - Linfeng Zhang; Guorong Wang; Zhiyuan Li; Lin Zhong; Qiang Fu; Jiwei Wu; Mengdi Wu; Dongmei Liang; Yuhang Zheng (Computers and Geotechnics, 2025)

Regulatory Roles of Exosomes in Aging and Aging-Related Diseases - Nanyin Xiao; Qiao Li; Guangyu Liang; Zonghao Qian; Yan Lin; Heng Zhang; Yangguang Fu; Xiao Yang; Cun-Tai Zhang; Jiankun Yang; Anding Liu (Biogerontology, 2025)

A laboratory study on wave Attenuation by oyster reefs-mangrove system - Beihan Jiang; Chenming Fu; Tuofu You; Yuanmin Sun; Xiaohe Lai; Feng Cai; Zhaoyang Hu; Xinqiang Wang; Liang Chen; Yitan Lin; Chunling Pan (Geo-Marine Letters, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Analysis of the effect of three different blanching processes on the flavor profile of peeled and unpeeled broad beans - Lu Shi; Xiaohui Fu; Menghua Lin; Yahui Li; Ying Liang; Zhiyong Zhang (Food Research International, 2025)

A systematic review on heavy metals in indoor air: Occurrence, spatial variation, and health risk - Ni Liang; Zekun Li; Jie Sun; Nan Fu; Guoliang Zhong; Xianbiao Lin; Kang Mao; Peng Zhang; Zhaofeng Chang; Dong Yang; Wei Du; Guofeng Shen; et al. (Building and Environment, 2025)

Application of aqueous two-phase extraction for separation and purification of various adeno-associated viruses - Xiao-Qian Fu; Hui-Yi Leong; Liang-Zhi Qiao; Jia-Nan Zhou; Wei Hu; Shan-Jing Yao; Dong-Qiang Lin (Biotechnology Letters, 2025)

Inactivated LMBV vaccine with nano‑aluminum adjuvant provided immune protection in largemouth bass (Micropterus Salmoides) - Xia Luo; Ruoxuan Wang; Baofu Ma; Ouqin Chang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Lihui Liu; Aijun Lv; Ningqiu Li (Aquaculture, 2025)

A boundary enforcement method for the truncated ship structure model during underwater contact explosion experiments - Liang Zhang; Xin Lin; Hong-Na Yang; Fu-Ren Ming (Ocean Engineering, 2025)

Mechanism and controlling factors of mass transport complexes migration: A case study of the mass transport complexes in the taranaki deep water basin, New Zealand - Yongsheng Zhou; Wei Wu; Jianwei Feng; Guangxu Wang; Aihua Fu; Shiqin Liang; Lulu Wu; Qingchao Li; Weiqing Liu; Zhendong Feng; Changsong Lin; Panpan Chen; et al. (Geomorphology, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Molecular phylogeny of Podoscypha (Basidiomycota, Podoscyphaceae) with descriptions of four new species, inferred from nuclear rDNA sequences - Fu-Chang Huang; Jian-Tian Lin; Hai-Fu Zheng; Yun-Long Liang; Miao-Miao Li; Cheng-Pei Ding (Mycological Progress, 2024)

Vision-based trajectory generation and tracking algorithm for maneuvering of a paddy field robot - Dengbin Fu; Zhiying Chen; Zhiqiang Yao; Zhanpeng Liang; Yinghu Cai; Chuang Liu; Zhenyu Tang; Caixia Lin; Xiao Feng; Long Qi (Computers and Electronics in Agriculture, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Differential response of soil bacteria and fungi to carbon and respiration components in abandoned grasslands on the Loess Plateau, China - Xingfang Tian; Ying Zhang; Yujie Liang; Rong Fu; Lin Sun; Zhouchang Yu; Jiayi Shi; Ahejiang Sailike; Hongjian Hao; Wei Zhang (Plant and Soil, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A naturaly attenuated largemouth bass ranavirus strain provided protection for Micropterus salmoides by immersion immunization - Xiaozhe Fu; Wenxian Li; Cong Liu; Xia Luo; Qiang Lin; Yinjie Niu; Hongru Liang; Baofu Ma; Ningqiu Li (Fish & Shellfish Immunology, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

A new high-order shock-capturing TENO scheme combined with skew-symmetric-splitting method for compressible gas dynamics and turbulence simulation - Tian Liang; Lin Fu (Computer Physics Communications, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Dynamic changes of key metabolites in Longjing green tea during processing revealed by widely targeted metabolomic profiling and sensory experiments - Lin Zeng; Yan-Qing Fu; Ying Gao; Fang Wang; Shuang Liang; Jun-Feng Yin; Marie-Laure Fauconnier; Lijing Ke; Yong-Quan Xu (Food Chemistry, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Actin-related protein MoFim1 modulated the pathogenicity of Magnaporthe oryzae by controlling three MAPK signaling pathways, appressorium formation, and hydrophobicity - Yun-Yun Wei; Xue-Ming Zhu; Xiao-Hong Liu; Fu-Cheng Lin; Shuang Liang (Physiological and Molecular Plant Pathology, 2024)

Bacterial assembly and succession patterns in conventional and advanced drinking water systems: From source to tap - Jie Liu; Renxin Zhao; Jie Feng; Wenjie Fu; Lijia Cao; Jiayu Zhang; Yusha Lei; Jiajin Liang; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Tissue factor pathway inhibitors disrupt structures of rhabdovirus/ranairidovirus and inhibit viral infection in Chinese perch, Siniperca chuatsi - Baofu Ma; Jingkang Li; Min Zhang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Xia Luo; Lihui Liu; Jianguo Su; Jin Zhou; Ningqiu Li (Fish & Shellfish Immunology, 2024)

Flexible fiber composite functional materials based on Fe-MOFs nanozyme catalytic activity for efficient point-of-use water disinfection - Hao Fu; Hao Li; Qiuwen He; Guangwu Du; Jianfang Li; Yuancheng Zhang; Yuntong Liang; Baofeng Lin (Chemical Engineering Journal, 2024)

Enhanced home-field advantage in deep soil organic carbon decomposition: Insights from soil transplantation in subtropical forests - Kuan Liang; Yong Lin; Tiantian Zheng; Fangchao Wang; Yuandong Cheng; Shennan Wang; Chao Liang; Fu-Sheng Chen (Science of The Total Environment, 2024)

Late Cenozoic uplift of the Liupan Mountains: Evidence from the Neogene loess deposits - Zhilin He; Yansong Qiao; Zhengtang Guo; Chaoqin Chen; Long Chen; Yang Fu; Ye Yang; Yanxia Liang; Xinru Lin; Guoqiao Xiao; Tao Zhan (Science China Earth Sciences, 2024)

Association between polycyclic aromatic hydrocarbons and infertility in U.S. women: National Health and Nutrition Examination Survey 2013–2016 - Xiaomei Wu; Suixiang Wang; Xiaoxiao Lin; Huanzhu Liang; Yingying Wu; Yuxuan Tan; Huixian Zeng; Qian Chen; Jie Wang; Feng Huang; Ziang Guo; Puyi Xing; et al. (Reproductive Toxicology, 2024)

Catalytic co-pyrolysis of coffee grounds and polyethylene: A comparison of HZSM-5 and HY - Jiawei Fu; Sen Lin; Bin Cai; Jiayu Liang; Zhibin Chen; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Chunxiao Yang; Yao He; Shuiyu Sun; Jingyong Liu (Fuel, 2024)

Punching shear behavior and corrosion resistance of composite slab-column connections reinforced by BFRP and steel rebar - Kai Qian; Yun-Hao Weng; Shi-Lin Liang; Feng Fu (Engineering Structures, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Occurrence of Cladosporium herbarum causing leaf spot on Avena sativa in China - Jiangui Zhang; Guiqin Zhao; Jikuan Chai; Liang Zeng; Wenlong Gong; Fu Ran; Xiumei Nie; Ruifang Zhang; Doudou Lin (Crop Protection, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Construction of a novel mathematical model for predicting pesticide release in soil and its application in rice pest control - Yuntong Liang; Fengqiong Jiang; Danxia Xu; Lihua Fu; Chuanhui Xu; Guohuan Huang; Baofeng Lin (Journal of Cleaner Production, 2024)

In vivo and in vitro, antiviral effects of two mixture of Chinese herbal drug active monomers against MSRV and LMBV in largemouth bass (Micropterus salmoides) - Yinjie Niu; Xiaozhe Fu; Qiang Lin; Hongru Liang; Xia Luo; Shaozhi Zuo; Lihui Liu; Ningqiu Li (Aquaculture, 2023)

Modelling of physical and mechanical properties and adiabatic temperature rise of cement-stabilized macadam - Tao Fu; Junlin Liang; Hongliu Rong; Yanliang Li; Ye Lin (Innovative Infrastructure Solutions, 2023)

Modeling of errors resulting from vehicle motions for CHZII mobile gravimeter and its performance verification during marine surveys - Hai-bo Tu; Jian-gang He; Ming Hu; Xing-hui Liang; Lei-jun Liu; Qin-qin Dong; Sun-jun Liu; Hui Zhang; Yong-tao Fu; Jun-jian Lang; Heng Sun; Lin-tao Liu (Applied Geophysics, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Iron blocks autophagic flux and induces autophagosomes accumulation in microglia - Deqiang Fu; Xingyue Liang; Yuxuan Jiang; Jieping Liu; Xiaosi Lin; Quan Yang; Xue Chen; Ping Huang; Wei Wang; Wenlin Wu (Food and Chemical Toxicology, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Multistage plate subduction controls intraplate volcanism and cratonic lithospheric thinning in Northeast Asia - Zhi Wang; Lijun Liu; Yi Fu; Liang Zhao; Jian Lin; Zhenmin Jin; Bo Zheng (Earth-Science Reviews, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Impact of COVID-19 pandemic on profiles of antibiotic-resistant genes and bacteria in hospital wastewater - Liang Zhao; Ziquan Lv; Liangqiang Lin; Xiaowei Li; Jian Xu; Suli Huang; Yuhua Chen; Yulin Fu; Changfeng Peng; Tingting Cao; Yuebin Ke; Xi Xia (Environmental Pollution, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The Toarcian Oceanic Anoxic Event in a shelf environment (Eastern Tethys): Implications for weathering and redox conditions - Ying Nie; Xiugen Fu; Jintong Liang; Hengye Wei; Zhengan Chen; Fei Lin; Shengqiang Zeng; Yunhao Wu; Yi Zou; Ahmed Mansour (Sedimentary Geology, 2023)

Enhancement of collapse-resistant capacity of non-seismically designed RC frames using various CFRP strengthening schemes - Shi-Lin Liang; Feng Fu; Zhi-Qiang Huang; Kai Qian (Engineering Structures, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

GS6.1 controls kernel size and plant architecture in rice - Hongyuan Zhao; Yu Fu; Guiquan Zhang; Yingqin Luo; Weifeng Yang; Xiaoya Liang; Lin Yin; Zhenwu Zheng; Yijun Wang; Zhan Li; Haitao Zhu; Jinyan Huang; et al. (Planta, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

Hydrochromic wood biocomposites for humidity and moisture detection - Yujie Chen; Chaozheng Liu; Zhaolun Liang; Lei Ye; Lin Liu; Zhipeng Liu; Xinhao Feng; Lloyd Donaldson; Tripti Singh; Xianxu Zhan; Jingquan Han; Qiliang Fu; et al. (Chemical Engineering Journal, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Seasonal and vertical variations of nutrient cycling in the world’s deepest blue hole - Lin Chen; Peng Yao; Zuosheng Yang; Liang Fu (Frontiers in Marine Science, 2023)
Nutrient cycling in anoxic seawaters is essential to marine ecosystem health and sustainability, yet it remains poorly understood. In this work, we analyzed dissolved inorganic nutrients as well as hydrochemical parameters in the Yongle Blue Hole (YBH) of the South China Sea in October 2019, which is the world’s deepest blue hole and is characterized by anoxia below the depth of 100 m. Nutrient data collected in two sampling campaigns in 2017 were also incorporated to examine the seasonal and vertical variations of nutrient cycling across steep redox gradients in the YBH. In response to the changes in redox conditions in different seasons, nutrients in the YBH showed significant seasonal variations. The nitrate maximum rose from a depth of 90 m in March 2017 to 60-80 m in October 2019, while the primary nitrite maximum concentration decreased from 0.5 μmol/L to 0.1 μmol/L. In October 2019, the nitrite decreased to below the detection limit at about 100 m, while in March 2017, it was 140 m. The regeneration of phosphate and silicate both started from around 40 m in October 2019 and from 80 m in March 2017. Silicate shows non-conservative adding behaviors relative to phosphate and DIN, and phosphate shows a similar but weaker adding behavior relative to DIN. The nutrient ratios also varied seasonally, especially for N/P, which fluctuated greatly on the surface at 80 m, while Si/N and Si/P fluctuated above 50 m. At the oxic-anoxic interface, extreme values of nutrient ratios were observed, and below 150 m, the N/P, Si/N, and Si/P were kept constant at about 17, 1.5, and 26, respectively. Seasonal and vertical variations of nutrient concentrations and ratios in the YBH reflect the impact of redox conditions on nutrient cycling in anoxic seawaters, especially during the transition from oxic to anoxic zone. And the high-resolution distributions of nutrients and hydrochemical parameters are helpful to better understand the nutrient cycling processes in highly dynamic coastal environments that are suffering deoxygenation.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Unveiling the effect of structural water on Zn-ion storage of polyoxovanadate for high-rate and long-life aqueous zinc ion battery - Huan He; Fu-Chun Pan; Xue-Wei Liang; Qiang Hu; Shude Liu; Jisong Hu; Seong Chan Jun; Dunmin Lin; Yusuke Yamauchi; Yu Huo (Chemical Engineering Journal, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Association between blood metal exposures and hyperuricemia in the U.S. general adult: A subgroup analysis from NHANES - Yuxuan Tan; Yingyin Fu; Feng Huang; Lin Wen; Xueqiong Weng; Huojie Yao; Huanzhu Liang; Mincong Kuang; Chunxia Jing (Chemosphere, 2023)

Identification of a 17β-estradiol-degrading Microbacterium hominis SJTG1 with high adaptability and characterization of the genes for estrogen degradation - Weiliang Xiong; Wanli Peng; Yali Fu; Zixin Deng; Shuangjun Lin; Rubing Liang (Journal of Hazardous Materials, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Extraction, purification, bioactivity and pharmacological effects of capsaicin: a review - Fengzhang Wang; Yong Xue; Lin Fu; Yongtao Wang; Minxia He; Liang Zhao; Xiaojun Liao (Critical Reviews in Food Science and Nutrition, 2022)

Lipofundin mediates major inhibition of intravenous propofol on phorbol myristate acetate and Escherichia coli-induced neutrophil extracellular traps - Ming-Shan Chen; Kung-Ssu Yang; Wen-Chun Lin; Chien-Liang Fang; Hsin-Fu Chen; Shew-Meei Sheu (Molecular Biology Reports, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Determination of the Non-metallic Elements in Herbal Tea by Inductively Coupled Plasma Tandem Mass Spectrometry - Liang Fu; Hualin Xie; Jianhua Huang; Lin Chen (Biological Trace Element Research, 2021)

A new 5α,8α-epidioxysterol with immunosuppressive activity from the South China Sea soft coral Sinularia sp. - Min Yang; Lin-Fu Liang; Heng Li; Wei Tang; Yue-Wei Guo (Natural Product Research, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Vertical variation in Vibrio community composition in Sansha Yongle Blue Hole and its ability to degrade macromolecules - Bei Li; Jiwen Liu; Shun Zhou; Liang Fu; Peng Yao; Lin Chen; Zuosheng Yang; Xiaolei Wang; Xiao-Hua Zhang (Marine Life Science & Technology, 2020)
With the advantages of wide distribution, fast growth, and broad metabolic spectrum to organic carbon compounds, Vibrio may play an important role in organic carbon cycling. However, the ecological roles of Vibrio in many marine environments have not been explored. Here, the world’s deepest ‘blue hole’, the Sansha Yongle Blue Hole (SYBH) in the South China Sea, which is a geographically semi-enclosed environment featuring unique chemical characters, was investigated. The abundance, diversity and carbon source utilization capability of Vibrio were studied by quantification and high-throughput sequencing of Vibrio specific 16S rRNA genes and cultivation methods. The abundance of Vibrio in water column of the SYBH ranged from 3.78 × 10 4 to 7.35 × 10 6 16S rRNA gene copies L −1 . Free-living Vibrio was more abundant than particle-associated Vibrio (~ 1.20 × 10 6 versus~ 2.68 × 10 5 gene copies L −1 ), indicating that Vibrio prefers a free-living life style. The Vibrio assemblages showed clear vertical stratification and could be divided into three groups: aerobic-transition, middle anaerobic and bottom anaerobic zones. Dissolved oxygen (DO), temperature, pH and salinity were the main environmental factors affecting the abundance and community composition. Cultivated Vibrio demonstrated a degrading capability to various macromolecular substrates, including starch, Tween 20/40/80, DNA, gelatin, alginate, casein, chitin, lecithin, κ-carrageenan, mannan, xylan and hyaluronic acid. This suggests that Vibrio could produce a variety of highly active extracellular enzymes. Our study provides new insights into the distribution pattern and possible role in carbon cycle of Vibrio in the unique environment of a ‘blue hole’.

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

The Ribosomal Protein RPLP0 Mediates PLAAT4-induced Cell Cycle Arrest and Cell Apoptosis - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Ming-Cheng Lee; Yi-Ying Lin; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2019)

The Mechanism of Rap1 Regulates N-cadherin to Control Neuronal Migration - Ciqing Yang; Xiaoying Li; Bichao Zhang; Sulei Fu; Shuanqing Li; Jianing Shen; Lihong Guan; Liang Qiao; Juntang Lin (Journal of Molecular Neuroscience, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

A new triterpene diglycoside from the roots of Bupleurum chinense DC. and its inhibitory effect on adipogensis in 3T3-L1 cells - Yujing Feng; Zhou-Wei Wu; Yanyan Luo; Liang Chen; Yufeng Cao; Lun Wang; Aftab Yaseen; Bin Chen; Ashfaq Ahmad Khan; Ming-Kui Wang; Guo-Lin Zhang; Xin-Feng Wang; et al. (Medicinal Chemistry Research, 2019)

Soil gas survey in and around Shanchiao fault of northern Taiwan for establishing continuous monitoring station - Arvind Kumar; Vivek Walia; Yi-Chun Sung; Shih-Jung Lin; Ching-Chou Fu; Kuo-Liang Wen (Acta Geophysica, 2018)

VPS9 domain‐containing proteins are essential for autophagy and endocytosis in Pyricularia oryzae - Xue‐Ming Zhu; Shuang Liang; Huan‐Bin Shi; Jian‐Ping Lu; Bo Dong; Qian‐Sheng Liao; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2018)
Summary Pyricularia oryzae is the causal pathogen of rice blast disease. Autophagy has been shown to play important roles in P . oryzae development and plant infection. The P. oryzae endosomal system is highly dynamic and has been shown to be associated with conidiogenesis and pathogenicity as well. To date, the crosstalk between autophagy and endocytosis has not been explored in P. oryzae . Here, we identified three P. oryzae VPS9 domain‐containing proteins, PoVps9, PoMuk1 and PoVrl1. We found that PoVps9 and PoMuk1 are localized to vesicles and are each co‐localized with PoVps21, a recognized marker of early endosomes. Deletion of PoVPS9 resulted in severe defects in endocytosis and autophagosome degradation and impaired the localization of PoVps21 to endosomes. Additionally, deletion of the PoMUK1 gene in the Δ Povps9 mutant background exhibited more severe defects in development, autophagy and endocytosis compared with the Δ Povps9 mutant. Pull‐down assay showed that PoVps9 interacts with PoVps21, PoRab11 and PoRab1, which have been verified to participate in endocytosis. Furthermore, yeast two‐hybrid and co‐immunoprecipitation assays confirmed that PoVps9 directly interacts with the GDP form of PoVps21. Thus, PoVps9 is a key protein involved in autophagy and in endocytosis.

Spike densities of the amygdala and neocortex reflect progression of kindled motor seizures - Yu-Lin Wang; Sheng-Fu Liang; Alvin W. Y. Su; Fu-Zen Shaw (Medical & Biological Engineering & Computing, 2018)

The biological features and genetic diversity of novel fish rhabdovirus isolates in China - Xiaozhe Fu; Qiang Lin; Hongru Liang; Lihui Liu; Zhibin Huang; Ningqiu Li; Jianguo Su (Archives of Virology, 2017)

GEM: a dynamic tracking model for mesoscale eddies in the ocean - Qiu-Yang Li; Liang Sun; Sheng-Fu Lin (Ocean Science, 2016)
The Genealogical Evolution Model (GEM) presented here is an efficient logical model used to track dynamic evolution of mesoscale eddies in the ocean. It can distinguish between different dynamic processes (e.g., merging and splitting) within a dynamic evolution pattern, which is difficult to accomplish using other tracking methods. To this end, the GEM first uses a two-dimensional (2-D) similarity vector (i.e., a pair of ratios of overlap area between two eddies to the area of each eddy) rather than a scalar to measure the similarity between eddies, which effectively solves the “missing eddy” problem (temporarily lost eddy in tracking). Second, for tracking when an eddy splits, the GEM uses both “parent” (the original eddy) and “child” (eddy split from parent) and the dynamic processes are described as the birth and death of different generations. Additionally, a new look-ahead approach with selection rules effectively simplifies computation and recording. All of the computational steps are linear and do not include iteration. Given the pixel number of the target region L, the maximum number of eddies M, the number N of look-ahead time steps, and the total number of time steps T, the total computer time is O(LM(N + 1)T). The tracking of each eddy is very smooth because we require that the snapshots of each eddy on adjacent days overlap one another. Although eddy splitting or merging is ubiquitous in the ocean, they have different geographic distributions in the North Pacific Ocean. Both the merging and splitting rates of the eddies are high, especially at the western boundary, in currents and in “eddy deserts”. The GEM is useful not only for satellite-based observational data, but also for numerical simulation outputs. It is potentially useful for studying dynamic processes in other related fields, e.g., the dynamics of cyclones in meteorology.

Dynamic soil-tunnel interaction in layered half-space for incident plane SH waves - Jia Fu; Jianwen Liang; Lin Qin (Earthquake Engineering and Engineering Vibration, 2016)

Bioethanol production by heterologous expression of two individual 1-FEH genes from Helianthus tuberosus in Saccharomyces cerevisiae 6525 - Xi Zhang; Huanhuan Xu; Ruixin Fu; Lijin Jin; Haiyan Zhao; Lin Wang; Mingxiang Liang (BioEnergy Research, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Cloning, expression, and characterization of Pseudomonas vesicularis MA103 β-1,3-xylanase in Escherichia coli ClearColi BL21(DE3) - Wen-Sing Liang; Tsuei-Yun Fang; Hong-Ting Lin; Tristan C. Liu; Wen-Jung Lu; Wen-Shyong Tzou; Shye-Jye Tang; Fu-Pang Lin; Shiu-Mei Liu; Chorng-Liang Pan (Fisheries Science, 2015)

Preparation and characterization of heparin hexasaccharide library with N-unsubstituted glucosamine residues - Qun Tao Liang; Jia Yan Du; Qing Fu; Jiang Hui Lin; Zheng Wei (Glycoconjugate Journal, 2015)

Identifications and removal of diurnal and semidiurnal variations in radon time series data of Hsinhua monitoring station in SW Taiwan using singular spectrum analysis - Arvind Kumar; Vivek Walia; Baldev Raj Arora; Tsanyao Frank Yang; Shih-Jung Lin; Ching-Chou Fu; Cheng-Hong Chen; Kuo-Liang Wen (Natural Hazards, 2015)

Distribution and phylogenetic analysis of Culex flavivirus in mosquitoes in China - Wenkai Liang; Xiaoxia He; Guifang Liu; Shaobai Zhang; Shihong Fu; Min Wang; Weixin Chen; Ying He; Xiaoyan Tao; Hongyue Jiang; Xiaojuan Lin; Xiaoyan Gao; et al. (Archives of Virology, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

Tree bark as a passive air sampler to indicate atmospheric polybrominated diphenyl ethers (PBDEs) in southeastern China - Xiaoxu Fu; Junxia Wang; Xiaoyu Zhou; Jingjing Deng; Yangcheng Liu; Wei Zhang; Lili Liu; Liang Dong; Kuangfei Lin (Environmental Science and Pollution Research, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Intraneuronal accumulation of Aβ42 induces age-dependent slowing of neuronal transmission in Drosophila - Jing-Ya Lin; Wen-An Wang; Xiao Zhang; Hai-Yan Liu; Xiao-Liang Zhao; Fu-De Huang (Neuroscience Bulletin, 2014)

Celastrol exerts synergistic effects with PHA-665752 and inhibits tumor growth of c-Met-deficient hepatocellular carcinoma in vivo - Hong-Lei Jiang; Jun-Zhe Jin; Dan Wu; Dong Xu; Guo-Fu Lin; Hao Yu; Dong-Yan Ma; Jian Liang (Molecular Biology Reports, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Erratum to: Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2013)

Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Xiao-liang Li; Chu-long Zhang; Wei-huan Fang; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Using EEFM (Excitation Emission Fluorescence Matrix) to Differentiate the Organic Properties of the Effluents from the Ozonated Biofilters - Wen-Liang Lai; Lih-Fu Chen; Shao-Wei Liao; Shu-Lin Hsu; Li-Ho Tseng; Chang-Ling Miaw (Water, Air, & Soil Pollution, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Absence of CYP2B6 promoter −82T>C mutation in Chinese as an additional factor for slow metabolism of drugs commonly used in infections - Ming-liang He; CK Lin; Kenneth Tong; Bingying Xu; Joseph JY Sung; Hsiang-fu Kung; Shui-shan Lee (European Journal of Clinical Pharmacology, 2006)

Reduced MTA1 Expression by RNAi Inhibits in Vitro Invasion and Migration of Esophageal Squamous Cell Carcinoma Cell Line - Haili Qian; Ning Lu; Liyan Xue; Xiao Liang; Xueyan Zhang; Ming Fu; Yongqiang Xie; Qimin Zhan; Zhihua Liu; Chen Lin (Clinical & Experimental Metastasis, 2005)

Regioselective Enzymatic Synthesis of Non-Steroidal Anti-Inflammatory Drugs Containing Glucose in Organic Media - Na Wang; Bo Kai Liu; Qi Wu; Jun Liang Wang; Xian Fu Lin (Biotechnology Letters, 2005)